Multicenter Analysis of the Factors Associated With Unplanned Extubation in the PICU. Issue 7 (September 2015) - Fitzgerald, Robert K.; Davis, Alan T.; Hanson, Sheila J.
Abstract : Objective: To identify factors associated with unplanned extubation in PICUs. Design: A prospective, case-controlled multicenter study. Setting: Eleven Pediatric Intensive Care Units collaborating through the National Association of Children's Hospitals and Related Institutions PICU focus group. Patients: Patients with unplanned extubation events and control patients without unplanned extubation. Interventions: Unplanned extubation events were prospectively tracked for 1 year at 11 centers. When an unplanned extubation occurred, up to four controls were randomly identified of other intubated patients in the unit. For each event and control, data associated with unplanned extubation events, reintubation, and outcomes were collected. Measurements and Main Results: One hundred eighty-nine unplanned extubation events occurred out of 25, 500 endotracheal tube days in the study (0.74 unplanned extubations/100 endotracheal days; 95% CI, 0.64–0.85), with 654 associated controls. Unplanned extubation rates ranged by site from 0.3 to 2.1 unplanned extubations/100 endotracheal days. Children less than 6 years had an increased rate of unplanned extubation (0.83 for < 6 yr vs 0.45 for ≥ 6 yr; p = 0.001). After multivariate analysis, inadequate patient sedation (odds ratio, 9.1; 95% CI, 4.5–18.5), loose or slimy endotracheal tube (odds ratio, 10.4; 95% CI, 5.0–22.2), a planned extubation in the next 12 hours (odds ratio, 2.3; 95% CI, 1.3–4.1), and a nurse pulled from another unit (odds ratio, 3.8; 95% CI, 1.4–9.9) were associated with unplanned extubation. Sixty percent of unplanned extubations required reintubation. Conclusions: The rate of unplanned extubation is higher in patients aged less than 6 years. Patient factors, such as decreased level of sedation, loose or slimy endotracheal tube, and staffing factors such as floating nurse from another unit, contribute to unplanned extubation in children. Abstract : Supplemental Digital Content is available in the text.